Perceptions of fieldwork in occupational therapy. (5th April 2016) - Ingwersen, Kate; Lyons, Nikki; Hitch, Danielle
Summary: Background: There are few studies in occupational therapy that compare the perceptions of supervisors and students regarding quality clinical placement programmes, and those that exist indicate substantial differences in the perceptions held by each group. Methods: This pilot study was conducted using a cross‐sectional descriptive design, with a single questionnaire distributed to occupational therapy students and clinical supervisors. A total of 40 questionnaires were returned: 17 from students and 23 from clinical supervisors. Results: Differences were found between the perceptions of occupational therapy students and clinical supervisors in response to four topics: preparation from the university for their placements; consistency across placement sites; instances of supervisors seeking feedback from students; and the burden associated with the placement‐related workload for clinicians. Differences were found between the perceptions of occupational therapy students and clinical supervisors in response to four topics Discussion: Different perceptions around preparation from universities and consistency across placement sites relate to the existing roles of each group: students are more aware of university preparation and clinical supervisors are more aware of organisational inconsistencies in their respective usual work environments. The discrepancy in the perceived seeking of feedback from students has also been reported in student debriefing sessions. The burdens perceived by clinical supervisors appear to be influenced by a belief that clinical education is an additional duty rather than a core role.